High prevalence of azole-resistant Aspergillus fumigatus in adults with cystic fibrosis exposed to itraconazole - Burgel, Pierre-Régis; Baixench, Marie-Thérèse; Amsellem, Michaël; Audureau, Etienne; Chapron, Jeanne; Kanaan, Reem; Honoré, Isabelle; Dupouy-Camet, Jean; Dusser, Daniel; Klaassen, Corné H; Meis, Jacques F; Hubert, Dominique; et al. (Antimicrobial agents and chemotherapy, 2012)
Aspergillus fumigatus is the most frequent fungus found in the sputum of cystic fibrosis (CF) subjects. Itraconazole is prescribed for allergic bronchopulmonary aspergillosis (ABPA) or Aspergillus bronchitis in CF subjects. We hypothesized that A. fumigatus isolates in the sputum of CF subjects with previous exposure to itraconazole was associated with higher prevalence of azole resistance. From June 2010 to April 2011, sputum samples from adult CF subjects at Cochin University Hospital (France) were examined systematically for the detection of A. fumigatus. MICs of A. fumigatus isolates against azoles were screened using Etest, and reduced susceptibility to azoles was confirmed using the CLSI broth microdilution method. A. fumigatus was isolated from the sputum of 131/249 (52.6%) adult CF subjects, and 47/131 (35.9%) subjects had received previous treatment with itraconazole. Reduced A. fumigatus susceptibility to itraconazole (MIC, ≥2 mg/liter) was confirmed in 6/131 (4.6%) subjects. All 6 isolates also had reduced susceptibility to posaconazole (MIC, ≥0.5 mg/liter), and 3/6 isolates had reduced susceptibility to voriconazole (MIC, ≥2 mg/liter). Mutations in the cyp51A gene were detected at positions previously implicated to cause resistance in 5 isolates. Azole-resistant A. fumigatus isolates were found in 5/25 (20%) subjects exposed to itraconazole within the previous 3 years. High rates of azole-resistant A. fumigatus isolates were present in adult CF subjects and were associated with recent itraconazole exposure. Although the clinical implications of these findings will require further studies, the cautious use of itraconazole in adult CF subjects can be recommended.